2021
DOI: 10.3389/fsoc.2021.648149
|View full text |Cite
|
Sign up to set email alerts
|

Rituals of Containment: Many Pandemics, Body Politics, and Social Dramas During COVID-19 in Pakistan

Abstract: Infecting millions of people, causing around two million deaths, and affecting billions of people worldwide during January 2021, the coronavirus 2019 (COVID-19) pandemic is not merely one pandemic but many. These many pandemics, which I identify herein, have revealed the overt and subtle entanglements among religion, science, and politics around COVID-19. Building on my current ethnographic research on COVID-19 using purposive sampling and interview guide in Pakistan, and borrowing from various anthropological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…Mental distress took many forms in these studies, including worry and concern about the future, anxiety about finances, guilt, depression, grief, fear, loneliness, and mistrust. The fear of contagion and death figured prominently in these studies, made more pronounced by social isolation and exaggerated media reports that spurred anxieties among the respondents [57,58,60,63,67,68,78,80]. Fear of the future was illustrated by a spectrum of concerns, as reported by researchers in Pakistan, centered on anxieties about the pandemic's effects on children, the nature of the post-COVID-19 world, and how many deaths would scar the future [59].…”
Section: Social and Psychological Effectsmentioning
confidence: 88%
See 2 more Smart Citations
“…Mental distress took many forms in these studies, including worry and concern about the future, anxiety about finances, guilt, depression, grief, fear, loneliness, and mistrust. The fear of contagion and death figured prominently in these studies, made more pronounced by social isolation and exaggerated media reports that spurred anxieties among the respondents [57,58,60,63,67,68,78,80]. Fear of the future was illustrated by a spectrum of concerns, as reported by researchers in Pakistan, centered on anxieties about the pandemic's effects on children, the nature of the post-COVID-19 world, and how many deaths would scar the future [59].…”
Section: Social and Psychological Effectsmentioning
confidence: 88%
“…Most studies in this review observed the psychosocial and economic impacts of the COVID-19 pandemic in LMIC communities around the world [57][58][59][60]63,64,[66][67][68]71,78,80]. The public health literature on pandemics and epidemics of infectious origin is rife with accounts of how these catastrophic disruptions to ordinary life are met by disarray and uncertainty, spawning fear and heightened anxiety [19,20] and often resulting in marginalization and stigma, as communities grapple with unknowns and avoid risks [8,[100][101][102][103][104].…”
Section: Social and Psychological Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important because the taboo of death also extends to "words taboo" and strongly contributes to grief stigmatization and disenfranchised grief symptoms. Also, although death rituals and mourning practices are highly dependent on the cultural context (5,36), the COVID-19 pandemic has created a global scenario with commonalities for people in all nations [i.e., (19,(37)(38)(39)(40)(41)(42)]. The most important commonalities are the psychological burden associated with confinement (43), the inability to say goodbye or to perform rituals according to believes and culture, and the measures of physical distancing, all of them considered risk factors for traumatic and disenfranchised grief in people with low resistance or resilience (19,35,44,45).…”
Section: Discussionmentioning
confidence: 99%
“…By January 2021, COVID-19 had already caused around 102 million cases and 2.19 million deaths worldwide (Johns Hopkins University, 2021). Yet from 2019 to 2021, differing forms of the pandemicor differing pandemicshave emerged (see Ali, 2021). James (2020) has rightly argued that 'the COVID-19 pandemic has morphed into what is now, in many ways, a new disease (COVID-20), even though resulting from the same agent, SARSCoV-2 [severe acute respiratory syndrome coronavirus 2]', thus, 'a vaccine, even an effective one, may not be the silver bullet'.…”
Section: Introductionmentioning
confidence: 99%